Penerapan Metode Eksperimen Materi Rangkaian Listrik Kelas VI di Sekolah Dasar - Wiwit Rahayu, Chandra; Titi Agustinah; Daimul Hasanah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to describe the application of experimental methods to electrical circuit material in elementary schools. Type of qualitative descriptive research. Data collection methods are observation, documentation, and questionnaires. Data analysis uses triangulation. Application of experimental methods to electrical circuit material in elementary schools by the planned steps. Observation results showed that the teacher had carried out learning activities by carrying out experimental method steps and making students active in learning. In documentation analysis, some students carried out activities according to the plan and understood the concepts well. In the questionnaire results, it was found that most students were interested in learning activities using experimental methods. Based on data analysis, it was found that the experimental method made students actively participate in learning activities and were interested in experimental activities.